The Ecology of Wonder in Romantic and Postmodern Literature - Economides, Louise; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book traces the aesthetic of wonder from the romantic period through contemporary philosophy and literature, arguing for its relevance to ecological consciousness. Most ecocritical scholarship tends to overshadow discussions of wonder with the sublime, failing to treat these two aesthetic categories as distinct. As a result, contemporary scholarship has conflated wonder and the sublime and ultimately lost the nuances that these two concepts conjure for readers and thinkers. Economides illuminates important differences between these aesthetics, particularly their negotiation of issues relevant to gender-based and environmental politics. In turn, readers can utilize the concept of wonder as an open-ended, non-violent framework in contrast to the ethos of domination that often surrounds the sublime.
Introduction: Wonder, Nature and Romanticism's Forgotten Way -- Chapter 1: Wonder and Romantic Ecology -- Chapter 2: Romanticism, Scientific Wonders, and the Technological Sublime -- Chapter 3: The Environmental Sublime and Ecological Melancholy -- Chapter 4: Wonder and Technē in an Age of Ecological Risk. .
Keywords: Postmodernism (Literature).; Literature, Modern-20th century; Literature, Modern-19th century